NAT10-Mediated N4-Acetylcytidine of RNA Contributes to Post-transcriptional Regulation of Mouse Oocyte Maturation in vitro - Xiang, Yuting; Zhou, Chuanchuan; Zeng, Yanyan; Guo, Qi; Huang, Jiana; Wu, Taibao; Liu, Jiawen; Liang, Qiqi; Zeng, Haitao; Liang, Xiaoyan (Frontiers in Cell and Developmental Biology, 2021)
N4-acetylcytidine (ac4C), a newly identified epigenetic modification within mRNA, has been characterized as a crucial regulator of mRNA stability and translation efficiency. However, the role of ac4C during oocyte maturation, the process mainly controlled via post-transcriptional mechanisms, has not been explored. N-acetyltransferase 10 (NAT10) is the only known enzyme responsible for ac4C production in mammals and ac4C-binding proteins have not been reported yet. In this study, we have documented decreasing trends of both ac4C and NAT10 expression from immature to mature mouse oocytes. With NAT10 knockdown mediated by small interfering RNA (siRNA) in germinal vesicle (GV)-stage oocytes, ac4C modification was reduced and meiotic maturation in vitro was significantly retarded. Specifically, the rate of first polar body extrusion was significantly decreased with NAT10 knockdown (34.6%) compared to control oocytes without transfection (74.6%) and oocytes transfected with negative control siRNA (72.6%) (p<0.001), while rates of germinal vesicle breakdown (GVBD) were not significantly different (P=0.6531). RNA immunoprecipitation and high-throughput sequencing using HEK293T cells revealed that the modulated genes were enriched in biological processes associated with nucleosome assembly, chromatin silencing, chromatin modification and cytoskeletal anchoring. In addition, we identified TBL3 as a potential ac4C-binding protein by a bioinformatics algorithm and RNA pulldown with HEK293T cells, which may mediate downstream cellular activities. Taken together, our results suggest that NAT10-mediated ac4C modification is an important regulatory factor during oocyte maturation in vitro and TBL3 is a potential ac4C-binding protein.